2014
DOI: 10.1002/ana.24193
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous enhancement of excitation and postburst inhibition at the end of focal seizures

Abstract: Our findings support the concept that focal seizures are terminated by the simultaneous and opposing enhancement of excitation (burst activity) in addition to postburst inhibition. We hypothesize that a seizure stops when postburst inhibition becomes large enough to prevent reactivation of excitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 71 publications
4
32
0
Order By: Relevance
“…3). Analysis of responses to local stimulation just suprathreshold for burst generation during focal seizures recorded in the isolated guinea pig brain preparation confirmed that interburst intervals correlated with an inhibition/depression lasting 1-2 sec (Boido et al 2014b). These data show that conflicting enhancement of both excitation and the ensuing inhibition characterize the end of a focal seizure and suggest that long postburst depression during the late ictal phase may stop the seizure by preventing further reactivation of the network (Boido et al 2015).…”
Section: Seizure Maintenance and Terminationmentioning
confidence: 87%
See 1 more Smart Citation
“…3). Analysis of responses to local stimulation just suprathreshold for burst generation during focal seizures recorded in the isolated guinea pig brain preparation confirmed that interburst intervals correlated with an inhibition/depression lasting 1-2 sec (Boido et al 2014b). These data show that conflicting enhancement of both excitation and the ensuing inhibition characterize the end of a focal seizure and suggest that long postburst depression during the late ictal phase may stop the seizure by preventing further reactivation of the network (Boido et al 2015).…”
Section: Seizure Maintenance and Terminationmentioning
confidence: 87%
“…The seizure is characterized by fast activity at onset, followed by tonic activation, and terminates with bursting activity that progressively slows down before seizure end. The closing phase of the seizure correlates with a progressive increase in interburst interval, measured in the shaded area outlined on the EEG trace (see Boido et al 2014b). TLE, temporal lobe epilepsy.…”
Section: Seizure Maintenance and Terminationmentioning
confidence: 99%
“…Neuronal activity during the bursting phase of a seizure becomes progressively larger in amplitude and the synchronous activation during each burst promotes a synchronous postburst depression/inhibition. We recently proposed that larger bursts induce progressively longer postburst depressions that may prevent further reexcitement of the network, thus leading to seizure termination and postseizure depression . The progressive increase in synchronization of bursting activity is likely mediated by local tissue phenomena, such as release of inhibitory transmitters/modulators, changes in extracellular ions and other mechanisms .…”
Section: Discussionmentioning
confidence: 99%
“…Our electrophysiological data show that during b‐early CA1 is the first activated structure, whereas in b‐late RE is taking the leading role. The recruitment of hippocampal synchronization during the bursts observed in the late part of a seizure could promote the increase in bursting excitation—and the subsequent postburst depression—that leads to seizure termination …”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the epileptic tissue has different responses to high‐ frequency stimulation in comparison to healthy brain tissue . Recent reports confirm the possibility of extracting active electrographic markers from epileptic areas with different stimulation protocols . In Bellistri et al., the analysis of responses to direct brain stimulation performed for diagnostic purposes during invasive stereo‐EEG studies with intracranial electrodes demonstrated that high‐frequency stimulation (HFS) at 50 Hz evoked high‐frequency responses in the gamma range (60–80 Hz), mainly in epileptogenic areas (accuracy rate 87% and sensitivity rate 94.5%) .…”
Section: What More Can We Learn From Our Patientsmentioning
confidence: 95%